2021
DOI: 10.1001/jamanetworkopen.2021.22692
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of HIV Preexposure Prophylaxis Use Behaviors and HIV Incidence Among US Adults in an Integrated Health Care System

Abstract: Key Points Question What factors are associated with gaps in the HIV preexposure prophylaxis (PrEP) continuum of care and where in the continuum do HIV infections occur? Findings In this cohort of 13 906 insured adults linked to PrEP care, individuals aged 18 to 25, African American individuals, Latinx individuals, women, individuals with lower socioeconomic status, and individuals with a substance use disorder were more likely to experience gaps in the PrE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 53 publications
2
36
0
Order By: Relevance
“…Although we were unable to directly compare rates of PrEP counselling to other groups, the very low rates of PrEP counselling and prescription among this cohort are consistent with other studies that have shown inequitable PrEP care continuum outcomes among Black individuals [ 7 , 16 , 61 , 63 , 64 ] and highlight the urgent need to ensure equitable PrEP access among this priority population or risk potentiating existing HIV disparities rather than alleviating them. Further investigation is warranted to identify and remove barriers to provider‐, clinic‐ and system‐level PrEP implementation.…”
Section: Discussionsupporting
confidence: 72%
“…Although we were unable to directly compare rates of PrEP counselling to other groups, the very low rates of PrEP counselling and prescription among this cohort are consistent with other studies that have shown inequitable PrEP care continuum outcomes among Black individuals [ 7 , 16 , 61 , 63 , 64 ] and highlight the urgent need to ensure equitable PrEP access among this priority population or risk potentiating existing HIV disparities rather than alleviating them. Further investigation is warranted to identify and remove barriers to provider‐, clinic‐ and system‐level PrEP implementation.…”
Section: Discussionsupporting
confidence: 72%
“…Although we were unable to ascertain sexual behaviors and the true number of individuals in our study who may benefit from PrEP is not known, HIV and STI positivity in our cohort were similar to studies of MSM. 12,16,17 These data reflect how PrEP penetrance in transgender individuals is suboptimal. 18 Furthermore, we found that nearly 40% of those who started PrEP subsequently discontinued.…”
Section: Discussionmentioning
confidence: 88%
“…Initiation was defined as a pharmacy fill and persistence as having no period of time more than 120 days without PrEP in possession based on pharmacy records. 8,12 New HIV diagnoses were identified using an HIV registry at KPNC. 13 Participant demographics and receipt of cross-sex hormones and gender-affirming surgery were summarized using descriptive statistics.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is noteworthy as PrEP is highly effective in reducing the risk of acquiring HIV [ 11 ], but estimates suggest that only approximately 20% of the 1.2 million estimated people who would benefit from PrEP in the US are currently using it [ 12 ]. Globally, the proportion of persons on PrEP is even lower [ 13 , 14 ] and among individuals who initiate PrEP, many discontinue within a few months of starting the regimen [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%